Karya Roh Kudus dalam Keselamatan: Eksposisi Efesus 1:13-14 tentang Meterai dan Jaminan Bagi Orang Percaya - Choe, Jin Hee; Chandra, Tjahjadi; Mukti, Guntur Hari (Jurnal Teologi Amreta (ISSN: 2599-3100), 2025)
Ephesians 1:13–14 contains the concepts of the Holy Spirit as a seal and a guarantee of salvation, which have been interpreted in various ways across Christian traditions. This has raised theological questions about the precise meaning and contemporary relevance of these terms for believers today. The subject of this study is text of Ephesians 1:13–14, while the object is the theological understanding of the concepts of sphragis (seal) and arrabōn (guarantee) in the context of salvation. The purpose of this research is to clarify the meaning of these concepts and explore their implications for Christian faith and practice. This qualitative study employs an exegetical and biblical hermeneutic approach. Data were collected through library research of biblical texts and theological literature, and analyzed through linguistic, historical, and theological synthesis. The findings reveal that the Holy Spirit affirms the believer’s identity as God’s possession, assures an unshakable salvation, guarantees the fulfillment of the eschatological inheritance, and calls believers to live in holiness. In conclusion, the role of the Holy Spirit as seal and guarantee offers a robust theological foundation for the doctrine of salvation and provides spiritual encouragement for believers in their daily faith journey.